DEFORMATION STRENGTH CAMPURAN LATASTON YANG MENGANDUNG BIOASPAL UNTUK LALULINTAS BERAT - , AGUNG RAHMAN YASIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asphalt is petroleum processed as petroleum feedstock which is good for the manufacture of asphalt is petroleum which contains asphalt (asphaltene) and contains little paraffin.In general, the use of asphalt is produced by artificial asphalt PT.Pertamina.The reduction in raw material (crude oil) and production costs tend to be expensive to make an excuse to produce bitumen from other raw materials are cheaper and more efficient. The idea arose from the existence of an idea to make the bitumen from oil palm shell raw material called bio asphalt. The initial process begins with the manufacture of bio-asphalt pyrolysis process to get the tar and oil palm shell liquid smoke.After the results obtained from the pyrolysis process, is the process of distillation to vaporize the liquid smoke and get the residue (bio asphalt). Bio asphalt that has been obtained is then mixed with bitumen oil from Pertamina. Bio bitumen asphalt mixing the oil is 1% - 10% of the weight of asphalt oil to be tested. Tests performed include: penetration testing asphalt, asphalt density testing, testing softening point, and ductility testing, and testing to see how mixing marshall maximum bio bitumen asphalt into oil, and marshall testing to determine the optimum bitumen content (OBC) her. The conclusion is that the results of maximal mixing between oil and bitumen bioaspal that meets the requirements of the 99% oil and 1% asphalt bioaspal with value OBC (Optimum Asphalt Content) of 6.5%.Deformation of testing strength values obtained DS: 6.02 MPa, while the minimum requirement is 4 MPa, thus concluded that the samples meet the requirements